The given problem is equation.

\(\displaystyle{x}+{\frac{{{3}{x}-{1}}}{{{9}}}}-{4}={\frac{{{3}{x}+{1}}}{{{3}}}}\)

we need to solve the given equation.

\(\displaystyle{x}+{\frac{{{3}{x}-{1}}}{{{9}}}}-{4}={\frac{{{3}{x}+{1}}}{{{3}}}}\)

\(\displaystyle{\frac{{{9}{x}}}{{{9}}}}+{\frac{{{3}{x}-{1}}}{{{9}}}}-{\frac{{{4}\times{9}}}{{{9}}}}={\frac{{{3}{x}+{1}}}{{{3}}}}\)

\(\displaystyle{\frac{{{9}{x}+{3}{x}-{1}-{36}}}{{{9}}}}={\frac{{{3}{x}+{1}}}{{{3}}}}\)

Step 2

12x-37=3(3x+1)

12x-37=9x+3

12x-9x=37+3

3x=40

\(\displaystyle{x}={\frac{{{40}}}{{{3}}}}\)